Green site practices and environmental performance: how project complexity moderates the relationship (Construction Economics and Building, 2019)
The characteristics of a project that makes it hard to understand, predict, and manage its general behavior despite the availability of required information relating to the project dynamics is referred to as project complexity. A good knowledge of project complexity at the construction phase of a project, as well as a well thought out plan to manage complexity will determine how proficiently construction projects are planned, managed, and executed in an environmentally friendly manner. The level of complexity of construction projects to a large extent determines the performance or otherwise of the projects with regards to achieving specific environmental standards. At construction sites, the effects of adopting green site practices on environmental performance is largely dependent on the level of complexity inherent in the project’s construction processes. This study investigates the moderating effects of project complexity on the relationship between various green construction site practices and environmental performance of construction projects. A survey was conducted on class A contractors in Nigeria and 168 usable responses were received. The data were analyzed using the partial least squares structural equation modelling technique. The results show that project complexity moderates the relationship between waste management and environmental performance, and the relationship between materials management and environmental performance. But project complexity does not moderate the relationship between energy management and environmental performance. The study provides important theoretical and practical information for construction managers in understanding the dynamics involved in managing of projects with different degrees of complexity, while adopting certain green site practices with the aim of delivering projects with high degree of environmental performance.